Characterization of lubricating grease formulated from waste engine oil - Nurul Waheeda, Abdu Rahman (2021)
The generation and disposal of waste oil increase year by year are causing environmental problems as well as depletion of natural resources. One of the ways to tackle this problem is by converting waste oil into a product such as lubricating grease. This research aimed to formulate lubricating grease from waste engine oil (WEO) as no study done on producing grease by using a mixture of WEO from a different type. Oil treatment to remove contamination and characterisation (fluid properties, components level and component analysis) also carried out in order to make sure that WEO can be used as the grease base oil. The treatment process of WEO include sedimentation, filtration, and heating is able to remove the contaminants until allowable level and moisture, making it is suitable to be base oil in grease formulating. Analysis on formulatedsodium grease (SG) and fumed silica grease (FSG) (SG96, SG94, SG92, SG90, SG88, FG85, FG84, FG83, FG82, FG81 & FG80) showed that WEO content in grease is inversely proportional to grease consistency but directly proportional to oil bleeding and separation of the grease. SG96 and FG85 have the lowest consistency number which is NLGI 0 and SG88 and FG80 have the highest consistency number which is NLGI 4-5. The oil bleeding of the greases are within the limit except for FG84 in room temperature which is -16.48%. Oil separation test showed that all of the greases oil separation is within the limit except for FG85 which have 5.75%. the greases also showed a corrosion standard of class 1 when tested with copper strip. Based on a few requirement, SG94 and FSG83 are selected as a grease that fulfilled the required criteria and comparison with industrial grease showed that the selected grease properties is comparable to industrial grease properties. The selected grease with the addition of additives (Polytetrafluoroethylene (PTFE) and graphite) showed that grease properties do not change except for intended additives used characteristic. The changes can be seen only on Fourier-transform infrared spectroscopy (FTIR) spectrum of sodium grease when there a presence of peak in fingerprint region (<600 cm-1) of the grease. However, the presence of additives heavily influenced the tribological properties of the grease where sodium grease have a good anti-wear property compared to FS grease. Sodium grease without additives also showed a better antiwear properties compared to sodium grease with additives making the addition of additives in sodium grease to be irrelevance. This is different from FS grease where addition of additives showed that the anti-wear properties of the grease improved. However, the antiwear properties of both greases is still within the industrial standard. As a conclusion, the properties of greases produced from WEO is good and comparable to industrial standard, and addition of additives in grease formulation effect the tribological properties of the grease. It is recommended the collection of WEO is vary from different sources for future study.